The Effectiveness of Using Flipped Reading Method to Enhance Students’ Reading Comprehension - Putri Khaerani; Desi Nahartini (Universitas Islam Negeri Palopo, 2025)
Reading comprehension is an important literacy skill in the digital age, where students are required to understand, evaluate, and interpret large amounts of information accessed through technology. However, Indonesian students continue to show low reading performance, as reflected in the 2022 PISA results, which highlight the need for more effective learning approaches. Although previous studies have examined the flipped classroom method and reported positive student perceptions, most rely on qualitative or descriptive data, with limited research statistically measuring learning outcomes, particularly in narrative text comprehension at the secondary school level. Therefore, this study aims to test the effectiveness of the flipped reading method in improving the reading comprehension of eighth-grade students. A quasi-experimental design was used involving 64 students, consisting of an experimental group and a control group. Data were collected through pre-tests and post-tests and analyzed using IBM SPSS 25 with the Wilcoxon Signed-Rank Test and Mann–Whitney U Test due to the non-normal distribution of data. The Wilcoxon test showed a significant increase in both groups (Sig. < 0.001). However, the Mann–Whitney U test showed no statistically significant difference between the two groups (p = 0.313 > 0.05). The effect size calculated using Cohen's r was 0.13, indicating a small effect. These results indicate that the flipped reading method does not produce a significant improvement in students' reading comprehension than conventional teaching. Suggesting that this method does not offer strong instructional advantages for teaching narrative reading comprehension at the secondary school level.